Ligand and base additive effects on the reversibility of nucleophilic addition in palladium-catalyzed allylic aminations monitored by nucleophile crossover. Issue 5 (1st February 2017) - Holtzman, Bryan S.; Roberts, Eric T.; Caminiti, Nicholas S.; Fox, Jacob A.; Goodstein, Madison B.; Hill, Staci A.; Jia, Zitong B.; Leibler, Isabelle N.-M.; Martini, Michael L.; Mendolia, Gina M.; Nodder, Sarah B.; Costanza-Robinson, Molly S.; et al.
Graphical abstract: Highlights: Nucleophile crossover quantitates reversibility of benzylamine addition. DBU and Cs2 CO3 inhibit crossover/reversibility with all ligands tested. Cs2 CO3 causes much less elimination to dienes than DBU. Percent conversion analysis shows timing of crossover/reversibility. Results support reversibility as mechanism for base effects on enantioselectivity. Abstract: A nucleophile crossover experiment was used to monitor the reversibility of nucleophilic addition of benzylamine to π-allylpalladium complexes. Dppe, dppp, dppb, and PHOX showed more crossover than PPh3 and dppm in both DMF and dichloromethane. Crossover was inhibited by the addition of DBU or Cs2 CO3, but much less elimination to diene side products was observed with Cs2 CO3 . Analysis of percent crossover vs. percent reaction completion using the PHOX ligand revealed that with added DBU or Cs2 CO3 crossover only began occurring after 100% completion had been reached.